Asymmetric budding of viruses in epithelial monlayers: a model system for study of epithelial polarity. - Boulan, E R (1978)
Infection of two different lines of polarized epithelial cells grown as monolayers with several types of enveloped viruses results, for each virus type, in a characteristic asymmetric budding of virions. Influenza virus (WSN strain), simian virus 5, and Sendai virus bud exclusively from the free (apical) surface of the cells, while vesicular stomatitis virus acquires its envelope only from the basolateral plasma membrane. Because different viruses select specific domains of plasma membrane in the same cell type, virus-infected epithelial monolayers can provide an excellent model system for studies of the mechanisms that generate regional differences in the distribution of plasma membrane components of epithelial cells.